Evolusi Pemikiran Manajemen Strategik Sebelum Era 2000-An - waskito, jati; Harsono, Mugi (Universitas Muhammadiyah Surakarta, 2017)
By the 1960s, large companies moved from the emphasis on operations, budgeting and control areas to an emphasis on the complexity of evolving planning and environmental dynamism and the need for solutions to this situation from top managers demanding planning for the future and looking globally. This article aims to describe the evolution of strategic management thinking from the 1960s to 2000. Each decade has a dominant issue whose discussion is represented by a prominent strategist of his time. They are chosen because they lead to the concept of strategic thinking, tools, and certain techniques.